Knowledge Knots on the Spot: Colonial Archives through the Looking Glass of the Archival Turn – the Cases of Caracas and Buenos Aires - Fechner, Fabian (Anuario de Historia de América Latina, 2017)
The global history of knowledge which has developed in recent years is focused on what we know and how we know it. The analysis of global knowledge transfer not only depends on individuals and institutions that made the circulation of information possible, but also on the way documents were intentionally stored and organized. However, the question of how archives, libraries, and other repositories reorganized knowledge, connected disconnected events, and developed techniques of record keeping in a colonial situation has hardly been answered. European central archives are the better known side of information and communication processes, but the aspect of interconnectedness and mutuality in these processes is usually neglected. The main purpose of this paper is to explore the overseas part of the colonial archive, not the European center. As a case study, two Latin American local archives are chosen, the Franciscan Archive in Caracas and the Jesuit Archive in Buenos Aires. The archiving processes in both repositories clarify specific colonial archival genres and archival habits in oversea territories. With exemplary archive inventories as essential organizational tools and instruments for safekeeping we can develop a better understanding of how knowledge was created and how local governance was conceptualized.